Marital Rape di Kampung Nelayan: Pandangan Sosiologis - Ghony, M. Djunaidi (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2004)
This research of marital rape at fisherman community on Sendangbiru. By using the sociological paradigm and of the case approach and the descriptivequalitative analysis, this research find out that: (1) There are marital rape realities in fishennan community environment; (2) Some factors that pushing the marital rape are: so ciological, a n thropological and psychological factors that sustained by understanding of nonnative and textual of religion doctrine; (3) the Marrital rape can be enforcing rapist, physical and psychical victim, and prostitution rape, that is woman become